Soil microbial effects on tree seedling performance during forest secondary succession - Anita Weissflog; Bettina M. J. Engelbrecht; John R. Healey; Lars Markesteijn (Ecology, 2026)
Soil microbiota influence seedling survival and abundance in mature forests. However, their role in tree species turnover during secondary forest succession remains unclear, especially in species‐rich tropical forests. We conducted a shade house experiment to assess variation in the direction and strength of net soil microbial effects on seedling emergence, biomass growth, and mortality of seven tree species. We tested for effects of soil successional stage (0, 15, 25, and 115 years of forest recovery), tree species' association with successional stages (home stages where species peak in abundance vs. away stages), and light level (5% vs. 40% of daylight). We quantified net microbial effects as the ratio of seedling performance in live soil (including microbiota) versus sterilized and fungicide‐treated soil. We found net positive or net negative microbial effects on seedling performance in six of the seven tree species, highlighting the prevalence of microbial effects. Overall, fewer seedlings emerged and more died in live than sterilized soils, and under high than low‐light levels, although these effects varied greatly among tree species. We found no effect of soil successional stage on seedling performance. Tree species' association with successional stages, however, strongly affected seedling performance: Soil microbiota from a species' home successional stage increased the likelihood of seedling emergence by approximately 16% and reduced seedling mortality by approximately 36%. Our results suggest that soil microbiota exert tree species‐specific effects on seedling performance during secondary succession of tropical forest. Positive microbial effects on seedling emergence and survival in tree species' home successional stages may promote tree species' establishment and persistence at home stages and could thereby slow tree species turnover during forest recovery. While the generality of our results needs to be tested across forest ecosystems, they highlight the relatively unexplored role of soil microbiota in determining the pace and direction of successional plant community assembly and promote the development of microbial inoculation as a tool for restoration of functionality and biodiversity of forests globally.

Global and boreal estimates of woody aboveground biomass for 2020: Filling GEDI's northern data gap with ICESat-2 and Harmonized Landsat Sentinel-2 - L. Duncanson; P.M. Montesano; A. Neuenschwander; A. Zarringhalam; N. Thomas; D.M. Minor; M.A. Wulder; J.C. White; E. Guenther; T. Feng; V. Leitold; S. Hancock; et al. (Remote Sensing of Environment, 2026)

Integrating albedo offsets in reforestation decisions for climate change mitigation outcomes in 2050: A case study in the USA - Lucas K. Johnson; Zhiqiang Yang; Angela Erb; Ryan M. Bright; Grant M. Domke; Tracey S. Frescino; Crystal B. Schaaf; Sean P. Healey (Forest Ecology and Management, 2025)

Calibration of GEDI footprint aboveground biomass models in Mediterranean forests with NFI plots: A comparison of approaches - Adrián Pascual; Paul B. May; Aarón Cárdenas-Martínez; Juan Guerra-Hernández; Neha Hunka; Jamis M. Bruening; Sean P. Healey; John D. Armston; Ralph O. Dubayah (Journal of Environmental Management, 2025)

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Quantifying population-level conservation impacts for a perpetual conservation program on private land - Kaylan M. Kemink; Robert L. Pressey; Vanessa M. Adams; Sarah K. Olimb; Aidan M. Healey; Boyan Liu; Todd Frerichs; Randy Renner (Journal of Environmental Management, 2023)

Seasonal development of a tidal mixing front drives shifts in community structure and diversity of bacterioplankton - Nathan G. King; Sophie‐B Wilmes; Samuel S. Browett; Amy Healey; Allan D. McDevitt; Niall J. McKeown; Ronan Roche; Ilze Skujina; Dan A. Smale; Jamie M. Thorpe; Shelagh Malham (Molecular Ecology, 2023)
Bacterioplankton underpin biogeochemical cycles and an improved understanding of the patterns and drivers of variability in their distribution is needed to determine their wider functioning and importance. Sharp environmental gradients and dispersal barriers associated with ocean fronts are emerging as key determinants of bacterioplankton biodiversity patterns. We examined how the development of the Celtic Sea Front (CF), a tidal mixing front on the Northwest European Shelf affects bacterioplankton communities. We performed 16S‐rRNA metabarcoding on 60 seawater samples collected from three depths (surface, 20 m and seafloor), across two research cruises (May and September 2018), encompassing the intra‐annual range of the CF intensity. Communities above the thermocline of stratified frontal waters were clearly differentiated and less diverse than those below the thermocline and communities in the well‐mixed waters of the Irish Sea. This effect was much more pronounced in September, when the CF was at its peak intensity. The stratified zone likely represents a stressful environment for bacterioplankton due to a combination of high temperatures and low nutrients, which fewer taxa can tolerate. Much of the observed variation was driven by Synechococcus spp. (cyanobacteria), which were more abundant within the stratified zone and are known to thrive in warm oligotrophic waters. Synechococcus spp. are key contributors to global primary productivity and carbon cycling and, as such, variability driven by the CF is likely to influence regional biogeochemical processes. However, further studies are required to explicitly link shifts in community structure to function and quantify their wider importance to pelagic ecosystems.

Water motion as a conditioning mechanism to improve the yield of the sugar kelp Saccharina latissima (Phaeophyceae) - Louise Kregting; Emma Healey; Molly Crowe; Eoghan M. Cunningham (Algal Research, 2023)

Genome‐wide analysis facilitates estimation of the amount of male contribution in meiotic gynogenetic three‐spined stickleback ( Gasterosteus aculeatus ) - Mark C. Currey; Charline Walker; Susan Bassham; Hope M. Healey; Emily A. Beck; William A. Cresko (Journal of Fish Biology, 2023)
Gynogenetic embryos – those inheriting only maternal DNA – can be experimentally created by fertilizing eggs with radiation‐treated sperm containing inactivated paternal chromosomes. Diploidy in the zygotes can be maintained through prevention of the second meiosis or restored by preventing the first mitosis after the maternal chromosome complement has been replicated. These gynogenetic organisms are useful in many fields including aquaculture, evolutionary biology and genomics. Although gynogenetic organisms have been created in numerous species, the completeness of uni‐parental inheritance has often been assumed rather than thoroughly quantified across the genome. Instead, when tests of uni‐parental inheritance occur, they typically rely on well‐studied genetically determined phenotypes that represent a very small sub‐set of the genome. Only assessing small genomic regions for paternal inheritance leaves the question of whether some paternal contributions to offspring might still have occurred. In this study, the authors quantify the efficacy of creating gynogenetic diploid three‐spined stickleback fish ( Gasterosteus aculeatus ). To this end, the authors mirrored previous assessments of paternal contribution using well‐studied genetically determined phenotypes including sex and genetically dominant morphological traits but expanded on previous studies using dense restriction site‐associated DNA sequencing (RAD‐seq) markers in parents and offspring to assess paternal inheritance genome‐wide. In the gynogenetic diploids, the authors found no male genotypes underlying their phenotypes of interest – sex and dominant phenotypic traits. Using genome‐wide assessments of paternal contribution, nevertheless, the authors found evidence of a small, yet potentially important, amount of paternally “leaked” genetic material. The application of this genome‐wide approach identifies the need for more widespread assessment of paternal contributions to gynogenetic animals and promises benefits for many aspects of aquaculture, evolutionary biology and genomics.

Contaminants in fish from U.S. rivers: Probability-based national assessments - Leanne L. Stahl; Blaine D. Snyder; Harry B. McCarty; Thomas M. Kincaid; Anthony R. Olsen; Tara R. Cohen; John C. Healey (Science of The Total Environment, 2023)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

An Evaluation of Fish Tissue Monitoring Alternatives for Mercury and Selenium: Fish Muscle Biopsy Samples Versus Homogenized Whole Fillets - Leanne L. Stahl; Blaine D. Snyder; Harry B. McCarty; Tara R. Cohen; Kenneth M. Miller; Mark B. Fernandez; John C. Healey (Archives of Environmental Contamination and Toxicology, 2021)
Fish contaminant studies with human health protection objectives typically focus on muscle tissue, recognizing that fillets are the commonly consumed tissue fraction. Muscle biopsy punch sampling for mercury analysis has recently been used as an alternative to harvesting fish for fillets; however, there is limited information comparing fillet plug results to whole fillet results. This study was conducted to address that data gap and to test the applicability of plugs for monitoring associated with United States Environmental Protection Agency’s fish tissue-based mercury and selenium water quality criteria. The mercury phase included 300 fillet homogenates and 300 field-extracted plug samples from 60 fish, and the selenium phase included 120 fillet homogenates and 120 plugs from 30 fish. Both phases showed that there were no statistically significant differences between fillet plug and homogenized fillet results at the community level; however, a selenium plug monitoring alternative must employ a sufficiently sensitive analytical method and consider total solids. Plug and fillet sampling alternatives have inherent advantages and disadvantages. Fillet sampling provides sufficient mass to consider multiple contaminants but requires fish to be harvested. Plug sampling only provides adequate mass for a single analyte but may allow fish survival, although additional research is needed on survival following plug removal.

Smoke on the Water: Comparative Assessment of Combined Thermal Shock Treatments for Control of Invasive Asian Clam, Corbicula fluminea - Neil E. Coughlan; Ross N. Cuthbert; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Gina Y. W. Vong; Emma Healey; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Jaimie T. A. Dick (Environmental Management, 2021)
Suppression of established populations of invasive alien species can be a complex and expensive process, which is frequently unsuccessful. The Asian clam, Corbicula fluminea (Müller, 1774), is considered a high impact invader that can adversely alter freshwater ecosystems and decrease their socioeconomic value. To date, C. fluminea continues to spread and persist within freshwater environments worldwide, despite repeated management attempts to prevent dispersal and suppress established populations. As extensive C. fluminea beds can often become exposed during low-water conditions, the direct application of hot or cold thermal shock treatments has been proposed as suitable mechanism for their control. Further, mechanical substrate disturbance may enhance the efficacy of thermal shock treatments by facilitating exposures to multiple layers of buried clams. In the present study, we advanced these methods by assessing combined applications of both hot and cold thermal shock treatments for control of C. fluminea , using steam spray (≥100 °C; 350 kPa), low- or high-intensity open-flame burns (~1000 °C) and dry ice (−78 °C). In a direct comparison of raking combined with hot thermal shock applications, both steam and high-intensity open-flame treatments tended to be most effective, especially following multiple applications. In addition, when hot thermal treatments are followed by a final cold shock (i.e. dry ice), steam treatments tended to be most effective. Further, when dry ice was applied either alone or prior to an application of a hot shock treatment, substantial if not complete C. fluminea mortality was observed. Overall, this study demonstrated that combined applications of hot and cold thermal shock treatments, applied following the disruption of the substrate, can substantially increase C. fluminea mortality compared to separate hot or cold treatments.

APOE genotype influences P3b amplitude and response to smoking abstinence in young adults - Ryan Coppens; Norka E. Rabinovich; Raghuveer Kanneganti; Herman A. Diggs; Kristin Wiggs; Travis Healey; Jodi Huggenvik; Gregory M. Rose; David G. Gilbert (Psychopharmacology, 2021)

Environmentally responsive QTL controlling surface wax load in switchgrass - Jennifer Bragg; Pernell Tomasi; Li Zhang; Tina Williams; Delilah Wood; John T. Lovell; Adam Healey; Jeremy Schmutz; Jason E. Bonnette; Prisca Cheng; Lisa Chanbusarakum; Thomas Juenger; et al. (Theoretical and Applied Genetics, 2020)

Steam and Flame Applications as Novel Methods of Population Control for Invasive Asian Clam (Corbicula fluminea) and Zebra Mussel (Dreissena polymorpha) - Neil E. Coughlan; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Emma Healey; Jaimie T. A. Dick; Gina Y. W. Vong; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Ross N. Cuthbert (Environmental Management, 2020)
Control strategies for established populations of invasive alien species can be costly and complex endeavours, which are frequently unsuccessful. Therefore, rapid-reaction techniques that are capable of maximising efficacy whilst minimising environmental damage are urgently required. The Asian clam ( Corbicula fluminea Müller, 1774), and the zebra mussel ( Dreissena polymorpha Pallas, 1771), are invaders capable of adversely affecting the functioning and biodiversity of freshwater ecosystems. Despite efforts to implement substantial population-control measures, both species continue to spread and persist within freshwater environments. As bivalve beds often become exposed during low-water conditions, this study examined the efficacy of steam-spray (≥100 °C, 350 kPa) and open-flame burn treatments (~1000 °C) to kill exposed individuals. Direct steam exposure lasting for 5 min caused 100% mortality of C. fluminea buried at a depth of 3 cm. Further, combined rake and thermal shock treatments, whereby the substrate is disturbed between each application of either a steam or open flame, caused 100% mortality of C. fluminea specimens residing within a 4-cm deep substrate patch, following three consecutive treatment applications. However, deeper 8-cm patches and water-saturated substrate reduced maximum bivalve species mortality rates to 77% and 70%, respectively. Finally, 100% of D. polymorpha specimens were killed following exposure to steam and open-flame treatments lasting for 30 s and 5 s, respectively. Overall, our results confirm the efficacy of thermal shock treatments as a potential tool for substantial control of low-water-exposed bivalves. Although promising, our results require validation through upscaling to field application, with consideration of other substrate types, increased substrate depth, greater bivalve densities, non-target and long-term treatment effects.

Deep phylogeographic structure may indicate cryptic species within the Sparid genus Spondyliosoma - Niall J. McKeown; Michael P. Gwilliam; Amy J.E. Healey; Ilze Skujina; Warren M. Potts; Warwick H.H. Sauer; Paul W. Shaw (Journal of Fish Biology, 2020)
Two geographically nonoverlapping species are currently described within the sparid genus Spondyliosoma : Spondyliosoma cantharus (Black Seabream) occurring across Mediterranean and eastern Atlantic waters from NW Europe to Angola and S. emarginatum (Steentjie) considered endemic to southern Africa. To address prominent knowledge gaps this study investigated range‐wide phylogeographic structure across both species. Mitochondrial DNA sequences revealed deep phylogeographic structuring with four regionally partitioned reciprocally monophyletic clades, a Mediterranean clade and three more closely related Atlantic clades [NE Atlantic, Angola and South Africa (corresponding to S. emarginatum )]. Divergence and distribution of the lineages reflects survival in, and expansion from, disjunct glacial refuge areas. Cytonuclear differentiation of S. emarginatum supports its validity as a distinct species endemic to South African waters. However, the results also indicate that S. cantharus may be a cryptic species complex wherein the various regional lineages represent established/incipient species. A robust multilocus genetic assessment combining morphological data and detailing interactions among lineages is needed to determine the full diversity within Spondyliosoma and the most adequate biological and taxonomic status.

Genetic analysis provides insights into species distribution and population structure in East Atlantic horse mackerel ( Trachurus trachurus and T. capensis ) - Amy J. E. Healey; Matthew W. Farthing; Francis K. E. Nunoo; Warren M. Potts; Warwick H. H. Sauer; Ilze Skujina; Nathan King; Sophie de Becquevort; Paul W. Shaw; Niall J. McKeown (Journal of Fish Biology, 2020)
Two sister species of horse mackerel ( Trachurus trachurus and T. capensis ) are described that are intensively harvested in East Atlantic waters. To address long‐standing uncertainties as to their respective geographical ranges, overlap and intraspecific population structure this study combined genetic (mitochondrial DNA and microsatellite) analysis and targeted sampling of the hitherto understudied West African coast. mtDNA revealed two reciprocally monophyletic clades corresponding to each species with interspecies nuclear differentiation supported by F ST values. The T. trachurus clade was found across the north‐east Atlantic down to Ghana but was absent from Angolan and South African samples. The T. capensis clade was found only in South Africa, Angola and a single Ghanaian individual. This pattern suggests that both species may overlap in the waters around Ghana. The potential for cryptic hybridization and/or indiscriminate harvesting of both species in the region is discussed. For T. capensis mtDNA supports high gene flow across the Benguela upwelling system, which fits with the species' ecology. The data add to evidence of a lack of significant genetic structure throughout the range of T. trachurus though the assumption of demographic panmixia is cautioned against. For both species, resolution of stock recruitment heterogeneity relevant to fishery management, as well as potential hybridization, will require more powerful genomic analyses.

On the predictability of lake surface temperature using air temperature in a changing climate: A case study for Lake Tahoe (U.S.A.) - S. Piccolroaz; N. C. Healey; J. D. Lenters; S. G. Schladow; S. J. Hook; G. B. Sahoo; M. Toffolon (Limnology and Oceanography, 2018)
Can we predict long‐term trends of lake surface temperature based on air temperature alone? We explore this question by analyzing the performance of a hybrid model ( air2water ) as a predictive tool for defining scenarios of lake surface temperature in the framework of climate change studies. Employing Lake Tahoe (U.S.A.) as a case study, we apply the model using different air temperature datasets (in situ measurements, gridded observations, and downscaled General Circulation Models). Through a data‐driven calibration of the model parameters based on surface water temperature records, we show that air2water provides good performance (root mean square error ∼ 0.5°C, on a monthly scale) regardless of the input dataset. The model is able to accurately capture the historical long‐term trend and interannual fluctuations over decades (from 1969 to present), using only 7 yr of monthly measurements of surface water temperature for calibration. Additionally, when used to predict future surface water temperature of the lake, air2water produces the same projections irrespective of the air temperature dataset used to drive the model. This is certainly desirable, but not immediately expected when using a relatively simple model. Overall, the results suggest the high potential and robustness of air2water as a predictive tool for climate change assessment. Lake surface temperature warming of up to 1.1°C (RCP 4.5) and 2.9°C (RCP 8.5) was simulated at the end of the 21 st century during summer months in Lake Tahoe. Such a scenario, if realized, would lead to serious consequences on lake water chemistry, primary productivity, plankton community structure, and nutrient cycling.

Finding alternatives to swidden agriculture: does agroforestry improve livelihood options and reduce pressure on existing forest? - Syed Ajijur Rahman; Jette Bredahl Jacobsen; John Robert Healey; James M. Roshetko; Terry Sunderland (Agroforestry Systems, 2017)

Tree Culture of Smallholder Farmers Practicing Agroforestry in Gunung Salak Valley, West Java, Indonesia - Syed Ajijur Rahman; Terry Sunderland; James M. Roshetko; Imam Basuki; John R. Healey (Small-scale Forestry, 2016)

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

The Biaxial Biomechanical Behavior of Abdominal Aortic Aneurysm Tissue - Siobhan A. O’Leary; Donagh A. Healey; Eamon G. Kavanagh; Michael T. Walsh; Tim M. McGloughlin; Barry J. Doyle (Annals of Biomedical Engineering, 2014)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

The Relative Impact of Harvest and Fire upon Landscape-Level Dynamics of Older Forests: Lessons from the Northwest Forest Plan - Sean P. Healey; Warren B. Cohen; Thomas A. Spies; Melinda Moeur; Dirk Pflugmacher; M. German Whitley; Michael Lefsky (Ecosystems, 2008)

Pronounced reproductive skew in a natural population of green swordtails, Xiphophorus helleri - ANDREY TATARENKOV; CHRISTIANE I. M. HEALEY; GREGORY F. GRETHER; JOHN C. AVISE (Molecular Ecology, 2008)
For many species in nature, a sire's progeny may be distributed among a few or many dams. This poses logistical challenges — typically much greater across males than across females — for assessing means and variances in mating success (number of mates) and reproductive success (number of progeny). Here we overcome these difficulties by exhaustively analyzing a population of green swordtail fish ( Xiphophorus helleri ) for genetic paternity (and maternity) using a suite of highly polymorphic microsatellite loci. Genetic analyses of 1476 progeny from 69 pregnant females and 158 candidate sires revealed pronounced skews in male reproductive success both within and among broods. These skews were statistically significant, greater than in females, and correlated in males but not in females with mating success. We also compare the standardized variances in swordtail reproductive success to the few such available estimates for other taxa, notably several mammal species with varied mating systems and degrees of sexual dimorphism. The comparison showed that the opportunity for selection on male X. helleri is among the highest yet reported in fishes, and it is intermediate compared to estimates available for mammals. This study is one of a few exhaustive genetic assessments of joint‐sex parentage in a natural fish population, and results are relevant to the operation of sexual selection in this sexually dimorphic, high‐fecundity species.

Energy expenditures during spawning by chum salmon Oncorhynchus keta (Walbaum) in British Columbia - B. R. McVeigh; M. C. Healey; F. Wolfe (Journal of Fish Biology, 2007)
Physiological telemetry and proximate tissue analyses were used to assess energy expended by chum salmon Oncorhynchus keta on various behaviours during spawning in Kanaka Creek, British Columbia, Canada, and results were compared with published data on Fraser River sockeye salmon Oncorhynchus nerka , the only other species for which both types of measurements have been taken. Chum salmon arrived at the spawning grounds with body energy densities of 4·84 MJ kg −1 in males and 4·62 MJ kg −1 in females, lower than most sockeye salmon populations, and died with energy densities of c . 4 MJ kg −1 , similar to that observed in sockeye salmon and other salmonids. Moisture levels generally increased in body tissues over the spawning life, particularly in female gonads, and lipid levels decreased. Declines in protein observed over the spawning life of other Pacific salmon Oncorhynchus sp. were less evident in Kanaka Creek chum salmon. Holding behaviour constituted the dominant component of the activity schedule and energy budget of both sexes. After holding, the most expensive behaviours were nest digging in females and aggressive displays in males. Dominant males expended the most energy on behaviours each day, as indexed by oxygen consumption (3600 mgO 2 kg −1 ), while satellite males expended nearly as much (3504 mgO 2 kg −1 ) but females expended considerably less (2327 mgO 2 kg −1 ). Kanaka chum salmon engaged more frequently in energetically expensive reproductive behaviours than Stuart River sockeye salmon.

Effects of species, culture history, size and residency on relative competitive ability of salmonids - C. A. Blann; M. C. Healey (Journal of Fish Biology, 2006)
The relative competitive ability of juvenile farm and wild salmonids was investigated to provide insight into the potential effects of introduction of cultured salmon on wild Pacific salmonid ( Oncorhynchus ) species. Aquarium experiments involving equal contests ( i.e. size matched, simultaneously introduced individuals) indicated that two wild coho salmon Oncorhynchus kisutch populations were competitively equal to a farm coho salmon population. In equal contests between farm Atlantic salmon Salmo salar (Mowi strain) and these wild coho salmon populations or coastal cutthroat trout Oncorhynchus clarki clarki , Atlantic salmon were subordinate in all cases. When Atlantic salmon were given a residence advantage, however, they were competitively equal to both wild coho salmon populations, but remained subordinate to coastal cutthroat trout. When Atlantic salmon were given a 10–30% length advantage, they were competitively equal to one wild coho salmon population but remained subordinate to the other. In equal contests in semi‐natural stream channels, both wild coho and farm Atlantic salmon grew significantly more in the presence of the other species than when alone. It appears that coho salmon obtain additional food ration by out competing Atlantic salmon, whereas Atlantic salmon were stimulated to feed more in the presence of coho salmon competitors. These results suggest that wild coho salmon and cutthroat trout should out compete farm Atlantic salmon of a similar size in nature. As the relative competitive ability of Atlantic salmon improves when they have a size and residence advantage, should feral populations become established, they may exist on a more equal competitive footing owing to the long freshwater residence of Atlantic salmon.

Predicting Species Response to Disturbance from Size Class Distributions of Adults and Saplings in a Jamaican Tropical Dry Forest - K. P. McLaren; M. A. McDonald; J. B. Hall; J. R. Healey (Plant Ecology, 2005)

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

Energetics and morphology of sockeye salmon: effects of upriver migratory distance and elevation - G. T. Crossin; S. G. Hinch; A. P. Farrell; D. A. Higgs; A. G. Lotto; J. D. Oakes; M. C. Healey (Journal of Fish Biology, 2004)
Depending on population, wild Fraser River sockeye salmon Oncorhynchus nerka travel distances of 1100 km and ascend elevations ranging from near sea‐level to 1200 m to reach spawning areas. Populations embarking on distant, high elevation migrations ( i.e . Early Stuart, Chilko and Horsefly populations) began their upriver spawning migrations with higher densities of somatic energy ( c . 9·2 to 9·8 MJ kg −1 ) and fewer eggs ( c . 3200 to 3800) than populations making shorter, low elevation migrations ( i.e . Weaver and Adams; c . 7·1 to 8·3 MJ kg −1 gross somatic energy and c . 4300 to 4700 eggs). Populations making difficult upriver migrations also had morphologies that were smaller and more fusiform than populations making less difficult migrations, traits that may facilitate somatic energy conservation by reducing transport costs. Indeed, fish travelling long distances expended less somatic energy per unit of migratory difficulty than those travelling shorter distances (2·8 to 3·8 kJ v . 10–1400 kJ). Consistent with evolutionary theory, difficult migrations appear to select for energy efficiency but ultimately fish making more difficult migrations produce fewer eggs, even when differences in body length have been accounted for. Despite large among‐population differences in somatic energy at the start of upriver migration, all populations completed migration and spawning, and subsequently died, with c . 4 MJ kg −1 of energy remaining, a level which may reflect a threshold to sustain life.

The effect of exercise and captivity on energy partitioning, reproductive maturation and fertilization success in adult sockeye salmon - D. A. Patterson; J. S. Macdonald; S. G. Hinch; M. C. Healey; A. P. Farrell (Journal of Fish Biology, 2004)
Releasing a population of adult Fraser River sockeye salmon Oncorhynchus nerka from an energetically more expensive non‐feeding natural migration (1089 km, natal groups) and allowing them to sexually mature in either a moderate flow (captive exercise group) or a no flow (captive non‐exercise group) environment resulted in significant differences in body energy densities (MJ kg −1 ) among groups (ranked: initial natural migrator > non‐exercise > exercise > natal arrivals). Similarly, per cent body lipids were significantly lower in exercise females compared with non‐exercise females, experimentally confirming the central role lipid catabolism has in powering swimming. Although restricting exercise did result in greater body energy reserves at spawning, this did not result in a reallocation of energy to reproduction, as fecundity, egg size and gonad composition were unchanged among the groups. Furthermore, non‐exercise females had delayed maturity, lower egg deposition rates, and were more likely to die prior to egg ovulation than exercise females and natal spawners. Eggs from captive exercise adult females were more likely to survive to the eyed stage than eggs from captive non‐exercise females, but both captive groups had significantly lower egg fertilization success than natal spawners suggesting that confinement stress played a role in some of results presented. There were no significant differences in plasma levels of glucose, lactate, cortisol and reproductive hormones among the groups, but correlations among acute and chronic indicators of stress were significant among individuals. These results indicate that exercise during the late stages of maturation, as might occur normally, may be required for optimizing reproductive maturation and maximizing reproductive success.

Field‐based measurements of oxygen uptake and swimming performance with adult Pacific salmon using a mobile respirometer swim tunnel - A. P. Farrell; C. G. Lee; K. Tierney; A. Hodaly; S. Clutterham; M. Healey; S. Hinch; A. Lotto (Journal of Fish Biology, 2003)
Novel field measurements of critical swimming speed ( U crit ) and oxygen uptake ( M o 2 ) in three species of adult Pacific salmon Oncorhynchus spp. up to 3·5 kg in body mass were made using two newly designed, mobile Brett‐type swim tunnel respirometers sited at a number of field locations in British Columbia, Canada. Measurements of U crit , which ranged from 1· 68 to 2·17 body lengths s −1 , and maximum M o 2 , which ranged from 8·74 to 12·63 mg O 2 kg −1 min −1 depending on the species and field location, were judged to be of similar quality when compared with available data for laboratory‐based studies. Therefore high quality respirometry studies were possible in the field using adult wild swimming salmonids. In addition, the recovery of wild adult Pacific salmon from the exhaustive U crit swim test was sufficiently rapid that swimming performance could be repeated with M o 2 being reestablished. This result suggests that wild adult salmon are capable of carrying a moderate excess post‐exercise oxygen consumption without adversely affecting U crit , maximum M o 2 or swimming economy. Such capabilities may be extremely important for timely migratory passages when salmonids face repetitive hydraulic challenges on their upstream migration.

Swimming patterns and behaviour of upriver-migrating adult pink (Oncorhynchus gorbuscha) and sockeye (O. nerka) salmon as assessed by EMG telemetry in the Fraser River, British Columbia, Canada - Scott G. Hinch; Emily M. Standen; Michael C. Healey; Anthony P. Farrell (Hydrobiologia, 2002)

On-farm evaluation of the establishment of clonal rubber in multistrata agroforests in Jambi, Indonesia - S. E. Williams; M. van Noordwijk; E. Penot; J. R. Healey; F. L. Sinclair; G. Wibawa (Agroforestry Systems, 2001)

Patterns of gametic investment by female stream‐and ocean‐type chinook salmon - M. C. Healey (Journal of Fish Biology, 2001)
Investment in fecundity and egg size is compared among two types of chinook salmon Oncorhynchus tshawytscha : stream‐type, which undertake long, arduous oceanic and upstream migrations and often return to their natal rivers (where they do not feed)months before spawning, and ocean‐type, which undertake relatively short oceanic and upstream migrations and remain at sea feeding and accumulating energy until a few days or weeks before spawning. The coefficient of variation in egg size for both life‐history types was significantly less than variation in fecundity, reflecting the expected strong selection on egg size relative to egg number. Total investment in the gonad varied significantly among years in both life‐history types, apparently reflecting variation in oceanic feeding conditions. Stream‐type chinook were smaller in total body size and more than 1 year older than ocean‐type. Stream‐type also invested relatively less of their total body energy in eggs and produced smaller eggs than ocean‐type, reflecting the greater energetic cost of their longer migration and freshwater maintenance. These differences suggest that stream‐type chinook pay a considerable fitness penalty in reproductive output. This may be offset by the fact that stream‐type go to sea at larger size and migrate far offshore, thereby avoiding some of the mortality costs of oceanic migration.

Variations and phenotypic correlation of growth attributes of Calliandra calothyrsus in the Blue Mountains of Jamaica - M. A. McDonald; J. R. Healey; M. Jones (Agroforestry Systems, 2000)

Enhancing the Uptake of Chemotherapeutic Drugs into Tumors using an “Artificial Lymphatic System” - Gene R. DiResta; Jongbin Lee; John H. Healey; Steven M. Larson; Ehud Arbit (Annals of Biomedical Engineering, 2000)

“Artificial Lymphatic System”: A New Approach to Reduce Interstitial Hypertension and Increase Blood Flow, pH and pO 2 in Solid Tumors - Gene R. DiResta; Jongbin Lee; John H. Healey; Andrey Levchenko; Steven M. Larson; Ehud Arbit (Annals of Biomedical Engineering, 2000)

A methodological appraisal of the impact of different classification procedures used in three different phases of the australian rheumatoid arthritis twin survey - N. Bellamy; D. L. Duffy; P. Sambrook; R. R. C. Buchanan; P. M. Brooks; H. Dunckley; S. C. Healey; S. Mason; N. G. Martin (Inflammopharmacology, 1998)